2018
DOI: 10.3390/molecules23030572
|View full text |Cite
|
Sign up to set email alerts
|

Network Formation via Anion Coordination: Crystal Structures Based on the Interplay of Non-Covalent Interactions

Abstract: We describe the synthesis and the structural characterization of new H2L(CF3CO2)2 (1) and H2L(Ph2PO4)2 (2) compounds containing the diprotonated form (H2L2+) of the tetrazine-based molecule 3,6-di(pyridin-4-yl)-1,2,4,5-tetrazine. X-ray diffraction (XRD) analysis of single crystals of these compounds showed that H2L2+ displays similar binding properties toward both anions when salt bridge interactions are taken into account. Nevertheless, the different shapes, sizes and functionalities of trifluoroacetate and d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 39 publications
0
14
0
Order By: Relevance
“…However, in a medium of high Cl − concentration (0.10 M), such as the one we adopted for our measurements, the ability of the ligand chains to form hydrogen bonds with ClO 4 − and PF 6 − is lower than in pure water due to saturation with Cl − . As a matter of fact, the free energy changes (−12.0 to −13.7 kJ/mol) for ClO 4 − and PF 6 − binding by L3 (protonated and not-protonated) fall near, or slightly above, the upper limit (−12.0 kJ/mol) previously found for anion–π interactions in water [12,13,14], suggesting that some hydrogen bonding of the anion with chain protons is still active, while the free energy changes (−6.3 to −9.1 kJ/mol) for ClO 4 − binding by L4 (protonated and not-protonated) are close to the lower limit (−8.6 kJ/mol) in agreement with the loss of such a hydrogen bonding contribution.…”
Section: Resultsmentioning
confidence: 82%
See 1 more Smart Citation
“…However, in a medium of high Cl − concentration (0.10 M), such as the one we adopted for our measurements, the ability of the ligand chains to form hydrogen bonds with ClO 4 − and PF 6 − is lower than in pure water due to saturation with Cl − . As a matter of fact, the free energy changes (−12.0 to −13.7 kJ/mol) for ClO 4 − and PF 6 − binding by L3 (protonated and not-protonated) fall near, or slightly above, the upper limit (−12.0 kJ/mol) previously found for anion–π interactions in water [12,13,14], suggesting that some hydrogen bonding of the anion with chain protons is still active, while the free energy changes (−6.3 to −9.1 kJ/mol) for ClO 4 − binding by L4 (protonated and not-protonated) are close to the lower limit (−8.6 kJ/mol) in agreement with the loss of such a hydrogen bonding contribution.…”
Section: Resultsmentioning
confidence: 82%
“…As for supramolecular chemistry, electronic features of s-tetrazine, such as a positive quadrupole moment, a high molecular polarizability, dispersion forces, or even electron sharing, have recently inspired the possible use of this heteroaromatic ring as a functional group to bind anions, an assumption that found solid foundations on ab initio calculations [2,3,4,5] and on the experimental evidence that anion– s -tetrazine ring interactions play an active role in determining the architecture of some metalla-macrocycles [6,7]. More recently, it was shown that s -tetrazine rings do behave as a binding site for anions even in solution [8,9,10,11,12], the anion– s -tetrazine interaction emerging as a promising tool for the construction of anion receptors as well as for the self-assembling of anion coordination frameworks (ACF) and polymers (ACP) [13,14].…”
Section: Introductionmentioning
confidence: 99%
“…Among our recent contributions, we demonstrated the use of tetrazine-based ligands for the coordination of inorganic [15,16] and organic anions [17], emphasizing coordination of halide [18] and pseudohalide anions [19]. Stabilization of anion coordination networks [20], including polyiodide-dense ones [21], has been achieved with s-tetrazine-based ligands through anion-π interactions [22], building on previous evidences of the usefulness of anion-π forces for polyiodide stabilization in perfluoroarene-based systems [23]. We re-evaluated azacyclophanes as templating agents to orchestrate the synthesis of polyiodides: while Ilioudis and Steed [24] reported formation of highly charged polyhalides (e.g., I 4 2− ) with cyclophanes matching the size of iodide anions, we demonstrated that size mismatch can be used to some extent to make the organic ligand act as a mold for the template self-assembly of larger, low-valency polyiodides (e.g., I 7 − ), leading to extremely iodine-dense crystalline phases [25];…”
Section: Introductionmentioning
confidence: 99%
“…It is known that azines may act as π-acid ligands, which can bind anions above their centres according to their positive electrostatic potentials (ESPs) and their molecular quadrupole moments ( Figure 2) [35]. For example, we have recently shown that s-tetrazine-based ligands can form anion complexes [36] with both inorganic [37][38][39][40][41][42] and organic [43] anions featuring clear anion-π interactions. Spontaneous oxidation of iodide in solution and stabilisation of triiodide (I 3 − ) anions in the solid state were observed in the presence of these s-tetrazine based ligands [38], while bromide was found to interact with the rings of these π-acids, but no oxidation to Br 3 − was detected [39].…”
Section: Introductionmentioning
confidence: 99%